Anatomical study on skull of Tarentola mauritanica - Abdelgader K. Youssef; Ahmed M. Hamed (Scientific Journal of University of Benghazi, 2026)
The present work was conducted on the morphological characters and structures of the Tarentola mauritanica skull one of the common species in Gekkonidae family that found in Libya (north Africa). We found that this tarentola skull is depressed and modified as diapsids, its side of the cheek is widely open, presumably in relation to the loss of the lower and upper temporal archs, lacrimal and postparietal bones that are present in the diapsid ancestor. The present study showed that the brain case is composed of four occipital bones, supraoccipital, basioccipital and two exoccipitals beside the single occipital condyle. The premaxilla and frontal bones are single while maxillae, nasal, parietal, vomer and palatine are paired bones. Our study revealed that the pterygoids of the skull are separated with epipterygoids on both side, with small ectopterygoid and the absence of the interpterygoid. The bones that composed the frame of the orbit were, the frontal, prefrontal and posfrontal. Ventrally to the orbit, there is no jugal bone that connect between the maxilla and the quadrate. We found that the mandible is composed of five bones, namely from posterior to anterior: the articular hat articulate with the quadrate, the angular, supra-angular, coronoid and he dentary.